DNA damage induction during localized chronic exposure to an insoluble radioactive microparticle - Yusuke Matsuya (Nature Portfolio, 2019)
Abstract Insoluble radioactive microparticles emitted by the incident at the Fukushima nuclear power plant have drawn keen interests from the viewpoint of radiation protection. Cs-bearing particles have been assumed to adhere in the long term to trachea after aspirated into respiratory system, leading to heterogeneous dose distribution within healthy tissue around the particles. However, the biological effects posed by an insoluble radioactive particle remain unclear. Here, we show cumulative DNA damage in normal human lung cells proximal and distal to the particle (β-ray and γ-ray-dominant areas, respectively) under localized chronic exposure in comparison with uniform exposure. We put a Cs-bearing particle into a microcapillary tip and placed it onto a glass-base dish containing fibroblast or epithelial cells cultured in vitro. A Monte Carlo simulation with PHITS code provides the radial distribution of absorbed dose-rate around the particle, and subsequently we observed a significant change in nuclear γ-H2AX foci after 24 h or 48 h exposure to the particle. The nuclear foci in the cells distal to the particle increased even under low-dose-rate exposure compared with uniform exposure to 137Cs γ-rays, which was suppressed by a treatment with a scavenger of reactive oxygen species. In contrast, such focus formation was less manifested in the exposed cells proximal to the particle compared with uniform exposure. These data suggest that the localized exposure to a Cs-bearing particle leads to not only disadvantage to distal cells but also advantage to proximal cells. This study is the first to provide quantitative evaluation for the spatial distribution of DNA double strand breaks after the heterogeneous chronic exposure to a Cs-bearing particle in comparison with uniform Cs exposure.